Prevalence of Cockroaches in A Private Faculty Building/its Surrounding, with Emphasize on its Vectorial Capacity For Intestinal Parasite, Its Public Health Implication and Comparison of the Performance of several Traditional Baits - Forman E Siagian; Jessica Livina; I Made Bayu Surya Dana; Ekarini Daroedono; Ronny Ronny (Jurnal Ilmu Kedokteran, 2017)
Cockroach caused intestinal problem due to its mechanical vectorial capability. It can carry many parasites, withdiverse susceptibility patterns. Its number in the enviromenment determine the potential risk of health hazard tohuman. This cross-sectional, entomological survey-study aimed to determine its prevalence with emphasize on vectorialcapability, public heath implication and comparison of several traditional baits/ attractants used to trapped cockroach.During 4 months of sampling, 434 cockroaches were successfully trapped, and the prevalence of intestinal parasiteisolated was 77.9%,which comprise of several types of parasite. Cockroach also more attracted to brown sugar usedas baits/attractants. These findings confirmed the importance of keeping hygiene/sanitation practices that must bemaintain all the time.